2020
DOI: 10.1097/pcc.0000000000002118
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Ultrasound During Critical Illness in Children: Survey of Practices in Pediatric Neurocritical Care Centers*

Abstract: Objectives: The scope of transcranial Doppler ultrasound in the practice of pediatric neurocritical care is unknown. We have surveyed pediatric neurocritical care centers on their use of transcranial Doppler and analyzed clinical management practices. Design: Electronic-mail recruitment with survey of expert centers using web-based questionnaire. Setting: Survey of 43 hospitals (31 United States, 12 internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The broad range of clinical indications for TCD [encompassing almost all diseases in critically ill children for which the use of TCD has ever been described (18)] was an important finding of the present study. The recent web-based survey by LaRovere et al also reported that TCD was used to investigate a dozen or so conditions in clinical practice (37). There is great scope for TCD use beyond the evaluation of patients with primary neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The broad range of clinical indications for TCD [encompassing almost all diseases in critically ill children for which the use of TCD has ever been described (18)] was an important finding of the present study. The recent web-based survey by LaRovere et al also reported that TCD was used to investigate a dozen or so conditions in clinical practice (37). There is great scope for TCD use beyond the evaluation of patients with primary neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The early use of TCD (within 24 h of admission), its status as a first-line neuromonitoring tool, and the frequency of use during night shifts highlighted the ready availability of this technique. TCD therefore has the potential to become an influential neuromonitoring strategy in the PICU (37,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basilar artery vasospasms occurred in 3% of children with moderate TBI and 21% of children with severe TBI (38). A recent survey of practices in pediatric neurocritical care centers showed that 74% of centers used TCD for clinical care, often for determining timing of neuroimaging, manipulating CPP, and deciding whether to perform surgical interventions (39).…”
Section: Cerebral Blood Flowmentioning
confidence: 99%